2010
DOI: 10.3390/molecules15031232
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of α-, β-, and γ-Melanocyte Stimulating Hormone on Acetaminophen Induced Liver Lesions in Male CBA Mice

Abstract: Research over the past decade has indicated that melanocortin peptides are potent inhibitors of inflammation and a promising source of new anti-inflammatory and cytoprotective therapies. The purpose of the present paper is to compare protective effects of α-, β-, and γ-melanocyte stimulating hormone on acetaminophen induced liver lesions in male CBA mice. Acetaminophen was applied intragastrically in a dose of 150 mg/kg, and tested substances were applied intraperitoneally 1 hour before acetaminophen. Mice wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 27 publications
(53 reference statements)
2
23
0
Order By: Relevance
“…Fluorescence titration was performed with D-α-MSH enantiomer also, but it did not give satisfactory results in terms of the obtained data suggesting very weak (if any) binding under the same experimental conditions. The result of the fluorescence titration of D-α-MSH with LVKAT antisense peptide is consistent with the findings of Turčić et al [ 15 , 16 ] showing that D-α-MSH does not bind antibody to L-α-MSH.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Fluorescence titration was performed with D-α-MSH enantiomer also, but it did not give satisfactory results in terms of the obtained data suggesting very weak (if any) binding under the same experimental conditions. The result of the fluorescence titration of D-α-MSH with LVKAT antisense peptide is consistent with the findings of Turčić et al [ 15 , 16 ] showing that D-α-MSH does not bind antibody to L-α-MSH.…”
Section: Resultssupporting
confidence: 91%
“…We tested peptides on the experimental model of acetaminophen (APAP)-induced liver lesions in male CBA mice, a useful animal model of hepatitis often used for the screening of hepatoprotective drugs [ 32 , 33 , 34 ]. Turčić et al [ 15 , 16 ] recently showed that α-MSH, a well known melanocortin peptide with anti-inflammatory and cytoprotective properties, exhibits strong and dose dependent hepatoprotective effects in this model.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…9, 13 This system comprises multiple components, including five class A guanine nucleotide–binding protein (G protein)–coupled melanocortin receptors (MCRs) MC1R∼MC5R; endogenous antagonists; and peptide agonists derived from the anterior pituitary gland, including α-melanocyte-stimulating hormone (MSH), β-MSH, γ-MSH, and ACTH. 9, 13 Accumulating data demonstrate that melanocortins, 14 in particular α-MSH 15 and its synthetic mimetics, 16 possess a potent protective activity in acute injuries in multiple organ systems, 17, 18, 19 including the kidney. 15 Nevertheless, although α-MSH has similar MCR agonizing potency as its parent molecule ACTH, 9, 13 the effect of ACTH on AKI has been barely investigated.…”
mentioning
confidence: 99%